Epilepsy and coeliac disease in children: a narrative review - Lonoce, L.; Laschi, E.; Minerva, M.; Lotti, F.; Curcio, M. R.; Francioni, A.; Pacenza, M.; Grosso, S. (Frontiers in Pediatrics, 2026)
BackgroundNeurological symptoms have been reported as extraintestinal manifestations (EIMs) in 3%–10% of children diagnosed with Coeliac disease (CD). Specifically, the prevalence of epilepsy has been reported to be approximately 1% in pediatric patients with CD, and this population shows an increased risk of developing epilepsy. However, there is still no comprehensive review of epidemiological data, seizure semiology, and electroencephalographic findings of epilepsy in pediatric patients with CD.MethodsWe conducted a narrative review to provide the most recent data regarding prevalence of epilepsy in CD children, describe the typical seizure semiology reported in literature according to the recent classification of International League Against Epilepsy (ILAE) and illustrate the management of epilepsy in this specific population.ResultsEpidemiological data regarding the prevalence of epilepsy in CD children and vice versa are heterogenous due to different inclusion criteria considered in various studies. Overall, an increased risk of epileptic disorder in CD patients has been described in some studies. On the other hand, a higher risk of CD has been reported in children diagnosed with certain types of epileptic disorders [e.g., idiopathic generalized epilepsies]. In terms of seizure semiology, the majority of children with CD present with generalized tonic-clonic seizures or focal seizures, usually of temporal or occipital origin. However, few other patients may experience other types of seizures, such as typical and atypical absences. A subgroup of CD patients presenting with occipital seizures and occipital calcifications on neuroimaging can be diagnosed with CEC syndrome (CD, epilepsy and calcification). A different response to gluten free diet in terms of seizure control has been observed in CD patients.ConclusionsClinicians should be aware of this possible neurological EIMs of CD in order to facilitate early recognition and refer patients for further investigations when required.